The Purchasing Power Parity Criterion for Stabilizing Exchange Rates. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1989)
The use of purchasing power parity as a basis of fixing exchange rates among industrial countries, as proposed by McKinnon, is discussed and contrasted with alternative interpretations of the PPP doctrine. Major policy implications of such a regime are emphasized. Furthermore, a new technique for estimating PPP exchange rates which makes use of price pressure exerted by exchange deviation is introduced. This method is capable of solving the 'base-year' problem more satisfactorily than the traditional Cassel-Keynes methodology. Estimated yen/dollar and mark/dollar PPP exchange rates are close to estimates derived using other methods.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet